2018
DOI: 10.1530/eje-18-0356
|View full text |Cite
|
Sign up to set email alerts
|

Association between the metabolically healthy obese phenotype and the risk of myocardial infarction: results from the Kailuan study

Abstract: Objective: This study aimed to determine if the metabolically healthy obese (MHO) is associated with an increased risk of myocardial infarction (MI) in Chinese population. Design: The Kailuan study is a community-based prospective cohort study. Methods: BMI and metabolic syndrome (MetS) were assessed in 91 866 participants without a history of MI or stroke. Participants were categorised into six mutually exclusive groups according to the BMI-MetS status: normal weight (BMI: ≤ 18.5to < 24.0 kg/m 2 ) without Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
1
22
0
2
Order By: Relevance
“…Second, we first verified that MHO or MH-OW did not increase the risk for all-cause mortality in a Chinese population. At this point, the present study supported the concept that “all obesity is not created equally.” However, considering our previous finding that obesity was associated with a higher risk of myocardial infarction, even without measurable metabolic abnormalities ( 21 ), whether participants with the MHO or MH-OW phenotype should reduce their body weight needs further consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we first verified that MHO or MH-OW did not increase the risk for all-cause mortality in a Chinese population. At this point, the present study supported the concept that “all obesity is not created equally.” However, considering our previous finding that obesity was associated with a higher risk of myocardial infarction, even without measurable metabolic abnormalities ( 21 ), whether participants with the MHO or MH-OW phenotype should reduce their body weight needs further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found that obesity was associated with myocardial infarction in a Chinese population, regardless of whether measurable metabolic abnormalities were present ( 21 ). This finding was consistent with those in several reports that aimed to identify a healthy obesity phenotype related to cardiovascular diseases ( 23 25 ).…”
Section: Introductionmentioning
confidence: 96%
“…Напротив, в недавнем проспективном когортном китайском исследовании Kailuan (период наблюдения 8 лет), показано, что группа с МЗФО имела повышенный риск ИМ -ОШ=1,8 (95% ДИ 1,37;2,25), по сравнению с метаболически здоровой группой с нормальным весом, после корректировки по потенциально связанным факторам. Риск ИМ был значительно повышен в метаболически нездоровой группе: у лиц с нормальным весом он составил ОШ=1,6 (95% ДИ 1,28;2,05), у метаболически нездоровых лиц с избыточным весом -ОШ=1,9 (95% ДИ 1,67;2,35) и в группе МНФО -ОШ=2,1 (95% ДИ 1,70;2,49) по сравнению с МЗФО [15]. Таким образом, МЗФО в большинстве исследований показывает меньший риск развития ИМ, чем МНФО.…”
Section: Discussionunclassified
“…Body mass index (BMI) is a widely used parameter to de ne overweight and obese status in adults [3]. In China, individuals within a BMI range of 24.0-27.9 kg/m 2 are de ned as overweight and those with BMI≥28.0 kg/m 2 as obese [4].…”
Section: Introductionmentioning
confidence: 99%